2021
DOI: 10.3390/ani11030708
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing the Review: A Pilot Study of the Ethical Review Process of Animal Research in Sweden

Abstract: The use of animals in research entails a range of societal and ethical issues, and there is widespread consensus that animals are to be kept safe from unnecessary suffering. Therefore, harm done to animals in the name of research has to be carefully regulated and undergo ethical review for approval. Since 2013, this has been enforced within the European Union through Directive 2010/63/EU on the protection of animals used for scientific purposes. However, critics argue that the directive and its implementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Overall, review boards work completely independent due to federal regulations without having unified criteria (Jörgensen et al., 2021). In general, missing of the latter complicates the work of reviewers and does not guarantee an unbiased review process upon known criteria for the applicants.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, review boards work completely independent due to federal regulations without having unified criteria (Jörgensen et al., 2021). In general, missing of the latter complicates the work of reviewers and does not guarantee an unbiased review process upon known criteria for the applicants.…”
Section: Discussionmentioning
confidence: 99%
“…(Unfortunately, a retrospective harm-benefit analysis indicates that even existing harm-benefit guidelines are not followed in some studies [ 44 ]). At the present time, however, recommendations to include even this level of quantification [ 43 ] have not been adopted in the United States and implementation in the European Union remains problematic [ 56 ]. As noted above, without such quantification, review remains qualitative and largely subjective between IACUCs [ 52 ], and even within a single IACUC, especially over time as membership changes.…”
Section: Discussionmentioning
confidence: 99%
“…While this is true, the EU have reported that no Member State has initiated a safeguard clause since the Directive took effect in January 2013 [24]. The issue with severity limits across Member States, however, is the lack of guidance and definition of these terms, particularly what 'cannot be ameliorated' means and the level of suffering that has to take place for it to be 'severe' [25]. As there is little guidance, and what does exist is general rather than detailed and specific, there are concerns that there is 'considerable variation' as to how severity limits are applied [26].…”
Section: Severity Limits/categories and The Harm-benefit Assessmentmentioning
confidence: 99%
“…For example, research from Sweden reviewing applications for projects using animals in procedures found they were mainly not completed adequately and in line with the Directive. As for the project evaluation by the Swedish Animal Ethics Committees, only 4 out of 18 application reviews were deemed to satisfactorily mention harm and benefit and none included mention of the 3Rs [25].…”
Section: Transparency Of Researchmentioning
confidence: 99%